Efficacy and toxicity of a paediatric protocol in teenagers and young adults with Philadelphia chromosome negative acute lymphoblastic leukaemia: results from UKALL 2003. (18th December 2015) - Hough, Rachael; Rowntree, Clare; Goulden, Nick; Mitchell, Chris; Moorman, Anthony; Wade, Rachel; Vora, Ajay
Summary: Despite the substantial outcome improvements achieved in paediatric acute lymphoblastic leukaemia (ALL), survival in teenage and young adult (TYA) patients has remained inferior. We report the treatment outcomes and toxicity profiles observed in TYA patients treated on the UK paediatric ALL trial, UKALL2003. UKALL2003 was a multi‐centre, prospective, randomized phase III trial, investigating treatment intensification or de‐escalation according to minimal residual disease (MRD) kinetics at the end of induction. Of 3126 patients recruited to UKALL2003, 229 (7·3%) were aged 16–24 years. These patients were significantly more likely to have high risk MRD compared to 10–15 year olds (47·9% vs. 36·6%, P = 0·004). Nonetheless, 5‐year event‐free survival for the TYA cohort (aged 16–24 years) was 72·3% [95% confidence interval (CI): 66·2–78·4] overall and 92·6% (95% CI: 85·5–99·7) for MRD low risk patients. The risk of serious adverse events was higher in patients aged ≥10 years compared to those aged 9 or younger ( P < 0·0001) and novel age‐specific patterns of treatment‐related toxicity were observed. TYA patients obtain excellent outcomes with a risk‐ and response‐adapted paediatric chemotherapy protocol. Whilst those aged 10 years and older have excess toxicity compared with younger patients, the age association is specific to individual toxicities.